Hepatitis C Testing Strategies in a Correctional Setting. (4th October 2017) - Assoumou, Sabrina A; Wang, Jianing; Tasillo, Abriana; Yazdi, Golnaz Eftekhari; Tsui, Judith I; Hariri, Susan H; Vellozzi, Claudia J; Strick, Lara; Linas, Benjamin P
Abstract: Background: There is no widely accepted testing approach for Hepatitis C Virus (HCV) infection in correctional settings, and the majority of U.S. prisons do not provide routine testing. Given the high prevalence of HCV in this setting, effective strategies for testing in corrections are needed. Methods: We used data from the Washington State Department of Corrections (WADOC), which has implemented opt-out HCV testing for all inmates at intake, to assess the difference in yield between routine testing vs.. current recommendations for risk-based and birth cohort testing for individuals born between 1945 and 1965. We analyzed data from a retrospective cohort of individuals who entered WADOC from January 1, 2012 to July 7, 2016. We also calculated the liver fibrosis stage of individuals with chronic HCV, defined as having a detectable HCV viral load, using Aspartate aminotransferase to Platelet Ratio Index (APRI). Results: 24, 731 individuals (83%) had opt-out HCV antibody testing upon prison entry, and 4, 951 (20%) had a reactive test. Of those, 3, 797 (77%) were white, 4, 023 (81%) were male, and 51% of individuals with a reactive test had a history of any drug use, defined by self-report or a drug-related offense. 2407 (47%) had an HCV RNA performed, and of those 1730 (72%) had chronic HCV infection. The prevalence of HCV antibody positivity was higher in individuals born between 1945 and 1965 when compared with those outside of the birth cohort (44% vs. 16%); however, the majority of cases (72%) were diagnosed outside of the birth cohort. Up to 35% of those with a reactive test would have been missed with combined risk-based and birth cohort testing compared with routine opt-out testing of all inmates at intake. Among individuals with chronic HCV infection and available liver fibrosis staging, 369 (21%) had at least moderate fibrosis including 209 (12%) with severe fibrosis. In addition, 262 (21%) of individuals outside of the birth cohort without a history of drug use, had at least moderate liver fibrosis. Conclusion: Targeted testing practices in prisons likely miss a substantial proportion of persons living with HCV, and associated liver fibrosis. Routine testing at prison entry should be considered for inclusion in the national HCV elimination strategy. Disclosures: All authors: No reported disclosures.